Hubungan Riwayat Anemia dan Kurang Energi Kronis (KEK) pada Ibu Hamil dengan Kejadian Stunting - Iin Setiawati; Tiya Maulana (Universitas Faletehan, 2024)
In December 2018, the number of stunting cases in NTB was approximately 37.2% (around 150.000 children under five years). of 10 districts/cities in NTB, most cases of stunting were found in Sumbawa Regency, reaching 41.8%. The aim of this study was to analyze the relationship between history of chronic energy deficiency (CED) and anemia in pregnant women with stunting incidence. This research used analytical design with a cross-sectional approach. The sample size was 124 mothers who had child under five years at Palibelo Health Center, selected by using simple random sampling technique. The data collection used maternal child health (MCH) handbooks and observational sheets. The data was tested statistically by using chi-square test. The result showed that there was a correlation between a history of anemia and incidence of stunting (p value 0.000), yet there was no relationship between history of anemia and incidence of stunting (p value 0.605). The researchers suggested parents to be able to care for and provide various foods to their child to help in dealing with stunting incidents.